PROFILE OF CD14 PROTEIN EXPRESSION IN URINE OF PROSTATE CANCER PATIENTS: PRELIMINARY STUDY AS A NON-INVASIVE BIOMARKERS CANDIDATE DEVELOPMENT - hajid rahmadianto (Mandala Of Health, 2021)
Prostate cancer (Pca) is a malignancy with a high incidence and mortality accompanied by advanced stage conditions in Indonesia. The delay in diagnosis is due to the absence of specific non-invasive biomarkers that can detect Pca early. CD14 protein is known to play a major role in the occurrence of malignancy in Pca. However, the role and alterations expressions in the urine of Pca are unclear. This study uses an analytical observational study using urine samples to detect CD14 protein expression using Elisa.Twelve urine samples of Pca and BPH were collected after obtaining ethical clearance and informed consent to participate in this study. Bioinformatics analysis using the TCGA database determines how changes in CD14 expression in tissue samples and sequence changes due to mutations and their relationship with poor prognosis for patients.GO Functional Analysis was carried out to determine the mechanism and role of the CD14. Data analysis was performed using GraphPad PRISM version 6 (GraphPad Software Inc., La Jolla, CA) dan curve expert 1.4.patient characteristics showed the median age of Pca patients was 63.5 years compared to 64 years of BPH patients. Pca patients in the metastatic group dominant at ISUP grade 5 (25%).On average, Pca patients have higher CD14 rates (0.208 ng/mL) compared to BPH (0.114 ng/mL) (p <0.05).Alteration of CD14 expression is known to have a role in the inflammatory response and is closely related to poor prognosis with patient survival rates with increased CD14 expression (p < 0.5). The conclusion of this study shows an increase in CD14 protein expression in urine Pca and is related to changes in function and poor prognosis.